Mechanism of Vibration Energy Action on Dynamic Instability of Shock-Type Rockburst Carrier System - Lyu Pengfei; Cui Xuekai (Shock and Vibration)
In coal mining, the rockburst intensity triggered by the mine earthquake is often greater in the mining area, and the precursor information is more difficult to capture. In this paper, this kind of rockburst is called shock-type rockburst and studied as the research object. Based on the evolution process and the theoretical model of the carrier system, the energy criterion of the occurrence of shock-type rockburst was deduced based on the theories of mathematics and statistical physics. The results showed that the process of shock-type rockburst can go through four stages: inoculation stage, occurrence stage, development stage, and termination stage, and the secondary triggering phenomenon may occur in the occurrence stage. The theoretical model of the shock-type rockburst carrier system was constructed, and the key characteristic parameter of shock-type rockburst was put forward. Then, the energy of mine earthquake was quantitatively characterized in the form of kinetic energy of rock block. Through the combination of the two parameters, the energy criterion of shock-type rockburst was obtained as follows: once the energy of mine earthquake acting on the rockburst source area was 2%–9% of the static energy, shock-type rockburst can occur. Then, this criterion was verified by three typical cases. Finally, based on the distribution conditions of “red seam” overburden in the Yanzhou mining area of China, the secondary triggering principle of rockburst was expounded, that is, the secondary triggering principle of rockburst caused by the shear fracture and sliding settlement of “red seam” overburden. To sum up, a theoretical system for judging the instability of the shock-type rockburst carrier system was formed. This study provides a theoretical basis for earthquake prevention and disaster reduction in coal mining.